Extensive prokaryotic maintenance respiration in the sea influenced by osmoregulation - Wikner, Johan; Vikström, Kevin (Frontiers in Marine Science, 2023)
Microbial respiration is the major process consuming oxygen in the biosphere. The relative energy demand from growth of biomass or maintenance activities determines the regulation of respiration with impact on how the development of hypoxia and CO2 emissions is controlled. This coupling is crucial for understanding the life history and associated ecological interactions of microorganisms. However, the knowledge of rate and regulating factors of maintenance respiration in the biosphere is limited. In this study, we demonstrated significant relationships in marine field samples where the prokaryotic specific growth rate predicts cell-specific respiration, in accordance with theory from culture models, over a 10-fold salinity range. This enables the first reported direct estimates of maintenance respiration in nature to show a 6-fold variation between 0.12-0.62 fmol O2 cell-1 d-1, comprising 29-72% of prokaryotic specific respiration. The lowest maintenance respiration occurred at salinity close to physiological osmolarity, suggesting osmoregulation as one of the more energy-consuming maintenance activities. A conservative global estimate of maintenance respiration accounted for 66% of the total prokaryotic respiration in the ocean´s mixed layer. This means that maintenance activities dominate the use of the energy generated by prokaryotic respiration in the sea, where osmoregulation is one significant energy consumer. Consequently, maintenance respiration and its regulation must be included in ecological and biogeochemical models to accurately project and manage the development of hypoxia and CO2 emissions from the ocean.